2022
DOI: 10.5194/bg-19-3381-2022
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon loss in warmed subarctic grasslands is rapid and restricted to topsoil

Abstract: Abstract. Global warming may lead to carbon transfers from soils to the atmosphere, yet this positive feedback to the climate system remains highly uncertain, especially in subsoils (Ilyina and Friedlingstein, 2016; Shi et al., 2018). Using natural geothermal soil warming gradients of up to +6.4 ∘C in subarctic grasslands (Sigurdsson et al., 2016), we show that soil organic carbon (SOC) stocks decline strongly and linearly with warming (−2.8 t ha−1 ∘C−1). Comparison of SOC stock changes following medium-term (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
4
7
0
Order By: Relevance
“…In a century-long geothermal soil warming gradient in subarctic Canada, whole-soil SOC stocks have been found to decline by 3% per 1°C 24 in a deciduous forest. This was also observed for a grassland topsoil in a geothermal gradient in Iceland (2.8 Mg C ha − 1 °C) 25 . Finally, the Harvard Forest soil, the longestrunning soil warming experiment, lost about 3 Mg C ha − 1 °C− 1 in 26 years of warming, which is also similar to the estimated absolute values in the present study 26 .…”
Section: Discussionsupporting
confidence: 72%
“…In a century-long geothermal soil warming gradient in subarctic Canada, whole-soil SOC stocks have been found to decline by 3% per 1°C 24 in a deciduous forest. This was also observed for a grassland topsoil in a geothermal gradient in Iceland (2.8 Mg C ha − 1 °C) 25 . Finally, the Harvard Forest soil, the longestrunning soil warming experiment, lost about 3 Mg C ha − 1 °C− 1 in 26 years of warming, which is also similar to the estimated absolute values in the present study 26 .…”
Section: Discussionsupporting
confidence: 72%
“…In a century-long geothermal soil warming gradient in subarctic Canada, whole-soil SOC stocks have been found to decline by 3% per 1°C 23 in a deciduous forest. This was also observed for a grassland topsoil in a geothermal gradient in Iceland (2.8 Mg C ha − 1 °C) 24 . Finally, the Harvard Forest soil, the longestrunning soil warming experiment, lost about 3 Mg C ha − 1 °C− 1 in 26 years of warming, which is also similar to the estimated absolute values in the present study 25 .…”
Section: Discussionsupporting
confidence: 72%
“…At the same sites, soil warming accelerated SOM decomposition (Marañón‐Jiménez et al ., 2018; Walker et al ., 2018), resulting in decreased SOM stocks (Verbrigghe et al ., 2022), while the soil C–N ratio remained unaltered, suggesting that plants and microbes were not able to retain the mineralized N within the ecosystem. Warming thus induced substantial losses of soil N (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these hypotheses, we found that the increase in soil temperature reduced both below and aboveground production similarly and did not change root–shoot ratio (Figs 1 and 2). Our results revealed that, in contrast to what was expected (warming accelerating nutrient cycling and thereby stimulating productivity), warming induced a loss of soil nitrogen and an increase in soil bulk density (both driven by a substantial loss of SOM; Marañón‐Jiménez et al ., 2019; Verbrigghe et al ., 2022), which elicited a reduction in both below and aboveground productivity.…”
Section: Discussionmentioning
confidence: 99%